Minimizing the Delay Time of Data Transfer in Access Networks Using Queue Models - Vinodhini, G. Arul Freeda; Vidhya, V. (Asian Journal of Engineering and Applied Technology, 2015)
Modeling and performance evaluation are becoming critical issues in access networks. The upstream channel of cable access network regulated by request grant mechanism can viewed as a two stage tandem queue. The intention of this paper is to divide the capacity of the upstream data among the two stations to ensure minimum delay time by considering the first node as M/M/1 queue and second node as M/M/1 retrial queue.